Cytotoxic chemotherapy for pancreatic neuroendocrine tumors. (3rd May 2015) - Okusaka, Takuji; Ueno, Hideki; Morizane, Chigusa; Kondo, Shunsuke; Sakamoto, Yasunari; Takahashi, Hideaki; Ohno, Izumi; Shimizu, Satoshi; Mitsunaga, Shuichi; Ikeda, Masafumi
Abstract Advanced neuroendocrine tumors are incurable, and most patients will succumb to the disease. Chemotherapies with cytotoxic agents such as streptozocin, 5‐fluorouracil, or temozolomide have been frequently used as drug therapies for neuroendocrine tumors. Streptozocin, which is the only approved cytotoxic agent available for the treatment of this disease in many countries, has been considered a key agent for the treatment of advanced neuroendocrine tumors based on the results of phase III studies. However, the widespread acceptance of streptozocin‐based chemotherapy for this indication has been limited by concerns regarding toxicity. Recent prospective and retrospective studies showed the promising activity of a temozolomide‐based regimen, although an adequate prospective controlled study defining the role of temozolomide in the treatment of neuroendocrine tumors is lacking. The promising activity of cytotoxic agents awaits confirmation; solid evidence‐based recommendations and treatment decisions are needed for the optimal use of chemotherapy against this disease.